Remote biomass burning dominates southern West African air pollution during the monsoon - (:unkn) unknown (My University, 2019)
Vast quantities of agricultural land in southern and central Africa are burnt between June and September each year, which releases large concentrations of aerosols into the atmosphere. The resulting smoke plumes are carried west over the Atlantic Ocean at altitudes between 2 and 4 km. As only limited observational data in West Africa have existed until now, whether this pollution has an impact at lower altitudes has remained unclear. The Dynamics-Aerosol-Chemistry-Cloud Interactions in West Africa (DACCIWA) aircraft campaign took place in 5 southern West Africa during June and July 2016, with the aim of observing gas and aerosol properties in the region in order to assess anthropogenic and other influences on the atmosphere. Results presented here show that a significant mass of aged accumulation mode aerosol was present in the southern West African boundary layer, over both the ocean and the continent. A median dry aerosol concentration of 6.2 µg m (standard temperature and pressure (STP)) was observed over the Atlantic Ocean upwind of the major cities, 10 with an interquartile range from 5.3 to 8.0 µg m-3. This concentration increased to a median of 11.1 µg m-3 (8.6 to 15.7 µg m-3) in the immediate outflow from cities. In the continental air mass away from the cities, the median aerosol loading was 7.5 µg m-3 , with an interquartile range of 4.2 µg m-3. The accumulation mode aerosol population over land displayed similar chemical properties to the upstream population, which implies that upstream aerosol is a Atmos. Chem. Phys. Discuss., https://doi. 2 significant source of aerosol pollution over the continent. The upstream aerosol is found to have most likely 15 originated from central and southern African biomass burning. This demons
Keywords: African Research